Pengaruh Bauran Promosi Terhadap Keputusan Konsumen Dalam Pembelian Mie Instan Merek Sedaap Di Desa Dalu X A Kecamatan Tanjung Morawa - Anggraini, Cut Widya; Lubis, Tukimin (Expensive: Jurnal Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of the promotional mix on consumer decisions in purchasing Sedaap brand instant noodles in Dalu X A Village, Tanjung Morawa District. This study uses a type of quantitative research. The population in this study were the people of Dalu X A Village, totaling 250, with 154 respondents taking samples using the slovin formula. The results of this study were collected through a questionnaire which was analyzed using multiple linear regression. The sampling method used in this research is stratified random sampling. The results of this study indicate that X1 is significant by 0.000 <0.05, thus advertising has a positive and significant effect on consumer decisions, sales promotion X2 is significant by 0.000 <0.05, thus sales promotion has a positive and significant effect on consumer decisions, and publicity X3 is significant at 0.000 <0.05, thus publicity has a positive and significant effect on consumer decisions. Fcount is 98.520 > Ftable 2.43 and sig. 0.000 < 0.05. The results of the F test prove that advertising X1, sales promotion X2 and publicity X3 simultaneously have a positive and significant effect on Y's purchasing decisions.